Advected Air Mass Reservoirs in the Downwind of Mountains and Their Roles in Overrunning Boundary Layer Depths Over the Plains. Issue 16 (26th August 2019) - Pal, Sandip; Lee, Temple R.
Abstract: Atmospheric boundary layer depths (BLDs) over continental sites have long been meticulously characterized. However, a downwind‐footprint concept for BLDs over plains under the impact of seasonally and spatially changing horizontal advection of BLDs off elevated terrains has remained unexplored. For the first time, we provide observational evidence of the impact of mountains on regional BLDs using 25‐years (1991–2015) of rawinsonde‐retrieved afternoon BLDs over 22 sites located in the mountains' (Rockies and Appalachians) downstream. Results suggest that mountain‐advected air mass, elevated terrains, and wind play a significant role in modulating BLD variability "miles away" from terrains. We found significant BLD contrasts over the plains (400–1, 500 m) under mountain‐advected versus flatland‐advected flows pertaining to elevated mixed layers off the mountain ranges. The BLD contrasts were higher in the downwind of Rockies than the Appalachians, and higher BLD contrasts were observed in spring and summer (900–1, 500 m) than in fall and winter (100–500 m). These findings will help build advanced parameterizations in models where BLD simulations around complex terrain still remain a hurdle. Plain Language Summary: The study of Earth's atmospheric boundary layer is important for many applications, including improving weather and air quality forecasts. However, little is known about how the boundary layer behaves in the vicinity and "miles away" from mountains. In the present study, we investigated the variability in boundary layer depths in areas downwind of the Rocky Mountains and the Appalachian Mountains, using a novel technique recently developed to estimate the daytime maximum boundary layer depth from 25 years of observations derived from instrumented weather balloons. We found that boundary depths were much deeper when the wind was coming from the mountains, rather than from the nearby plains. Overall, our results underscore the importance of large‐scale transport on certain characteristics of the atmospheric boundary layer, in particular temperature and moisture at sites downwind of large mountains. Knowledge gained from this study helps us improve how to better represent boundary layer processes in weather forecasting models and understand better thunderstorm development occurring over and near mountainous regions. Key Points: Twenty‐five years of rawinsonde‐based boundary layer depth was investigated at sites downwind of the Rocky and Appalachian Mountains. Large differences were present in boundary‐layer depths due to the impact of elevated mixed layers advected off the mountains. The footprint of boundary layer depths over the plains is influenced by contrasting flows that change seasonally and spatially.